COOPERATION AND INDEPENDENCE IN ENGLISH LANGUAGE TEACHING: EDUCATIONAL THEORIES AND PRACTICAL SOLUTIONS - Ashurova Dildora Gafurovna (Bright Mind Publishing, 2025)
This article explores innovative cooperative strategies used in the process of teaching English and highlights the role of teachers in transforming students into independent learners. It also analyzes various methods for fostering learner autonomy and applies the theoretical frameworks of scholars such as Lev Vygotsky, Jean Piaget, Albert Bandura, John Dewey, and Howard Gardner. The theories of these researchers are presented to explain how to develop learners' ability to acquire knowledge independently. By understanding and implementing these processes in practice, educators can more effectively support students’ independent learning.